The anticancer drug tamoxifen is active against Trypanosoma cruzi in vitro but ineffective in the treatment of the acute phase of Chagas disease in mice - Danilo Ciccone Miguel; Marcela Lencine Ferraz; Rosana de Oliveira Alves; Jenicer KU Yokoyama-Yasunaka; Ana Claudia Torrecilhas; Alvaro José Romanha; Silvia RB Uliana (Memorias do Instituto Oswaldo Cruz, 2010)
The activity of the antineoplastic drug tamoxifen was evaluated against Trypanosoma cruzi. In vitro activity was determined against epimastigote, trypomastigote and amastigote forms of CL14, Y and Y benznidazole resistant T. cruzi strains. Regardless of the strain used, the drug was active against all life-cycle stages of the parasite with a half maximal effective concentration ranging from 0.7-17.9 µM. Two experimental models of acute Chagas disease were used to evaluate the in vivo efficacy of treatment with tamoxifen. No differences in parasitemia and mortality were observed between control mock-treated and tamoxifen-treated mice.